Effects of Psychiatric Disorders on Labor Market Outcomes: A Latent Variable Approach Using Multiple Clinical Indicators. (13th November 2015) - Banerjee, Souvik; Chatterji, Pinka; Lahiri, Kajal
Abstract: In this paper, we estimate the effect of psychiatric disorders on labor market outcomes using a structural equation model with a latent index for mental illness, an approach that acknowledges the continuous nature of psychiatric disability. We also address the potential endogeneity of mental illness using an approach proposed by Lewbel (2012) that relies on heteroscedastic covariance restrictions rather than questionable exclusion restrictions for identification. Data come from the US National Comorbidity Survey – Replication and the National Latino and Asian American Study. We find that mental illness adversely affects employment and labor force participation and also reduces the number of weeks worked and increases work absenteeism. To assist in the interpretation of findings, we simulate the labor market outcomes of individuals meeting diagnostic criteria for mental disorder if they had the same mental health symptom profile as individuals not meeting diagnostic criteria. We estimate potential gains in employment for 3.5 million individuals, and reduction in workplace costs of absenteeism of $21.6 billion due to the resultant improvement in mental health. Copyright © 2015 John Wiley & Sons, Ltd.